2020
DOI: 10.1108/ijlma-02-2020-0056
|View full text |Cite
|
Sign up to set email alerts
|

Independence and effectiveness in internal Shariah audit with insights drawn from Islamic agency theory

Abstract: Purpose This paper aims to examine bases of effectiveness in internal Shariah auditing undertaken in Islamic financial institutions (IFIs). Design/methodology/approach This paper is theoretical in approach taking, as its starting-point, an extensive literature review. From a general agency theory, an Islamic agency theory is articulated and then applied to ascertain attributes of internal Shariah audit effectiveness revolving around the concept of independence. Findings Effective internal Shariah auditing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 19 publications
1
20
0
7
Order By: Relevance
“…Istilah wakalah atau wikalah merupakan kata benda yang berasal dari kata wakala yang memiliki beberapa arti, termasuk melakukan suatu tugas atas nama orang lain atau menjadi wakil. Secara teknis wakalah mengacu pada kontrak yang di mana seorang muwakkil (pihak utama) memberikan wewenang kepada salah satu pihak sebagai wakil (agen) untuk melakukan tugas atasnamanya (Khalid & Sarea, 2020). Menurut AAOIFI (2017), wakalah adalah tindakan dari satu pihak yang mendelegasikan yang lain untuk bertindak atas Namanya dalam apa yang dapat menjadi pokok bahasan pendelegasian.…”
Section: Teori Keagenan Dalam Perspektif Islamunclassified
See 2 more Smart Citations
“…Istilah wakalah atau wikalah merupakan kata benda yang berasal dari kata wakala yang memiliki beberapa arti, termasuk melakukan suatu tugas atas nama orang lain atau menjadi wakil. Secara teknis wakalah mengacu pada kontrak yang di mana seorang muwakkil (pihak utama) memberikan wewenang kepada salah satu pihak sebagai wakil (agen) untuk melakukan tugas atasnamanya (Khalid & Sarea, 2020). Menurut AAOIFI (2017), wakalah adalah tindakan dari satu pihak yang mendelegasikan yang lain untuk bertindak atas Namanya dalam apa yang dapat menjadi pokok bahasan pendelegasian.…”
Section: Teori Keagenan Dalam Perspektif Islamunclassified
“…Konsep khalifah (wakil) dan Ihsan berpengaruh positif pada hubungan yang diatur oleh teori keagenan Islam. Sejalan dengan konsep khilafah, akuntanbilitas lebih menekankan pada kewajiban daripada hak karena jika kewajiban dipenuhi oleh semua orang, kepentingan pribadi secara otomatis berada dalam batas-batas dan hak semua tidak diragukan lagi dilindungi (Chapra, 1992 pada Khalid & Sarea, 2020).…”
Section: Teori Keagenan Dalam Perspektif Islamunclassified
See 1 more Smart Citation
“…According to Khalid & Sarea (2021), effectiveness is the ability of a company to achieve goals or final results that have been set precisely which are used as applicable standards to reflect a company that has shown operational effectiveness. Referring Amin (2020), the definition of effectiveness is a match between the person's effort in carrying out the task with the intended target or the comparison between the goal achievement with the plan or a comparison of real results with the results that have been planned.…”
Section: Effectiveness Theorymentioning
confidence: 99%
“…Furthermore, although corporate governance in IFIs has attracted much attention in the literature, very little is written on SA, its effectiveness, determinants and outcomes. Several researchers (Khalid and Sarea, 2021; Omar, 2019) reported that there is limited work on this topic available in the literature. The existing empirical studies have mainly focused on countries such as Malaysia (Mohd Ali et al , 2018; Najeeb and Ibrahim, 2014) and Indonesia (i.e.…”
Section: Introductionmentioning
confidence: 99%